Design Of Sunlight, Humidity, And Temperature Measurement Systems With Data Acquisition For Iot-Based Solar Panel Placement - Satrio Widianto Utomo; Minarto Minarto; Ismi Kaniawulan (Institut Pendidikan Indonesia, 2023)
The Internet of Things (IoT) is a concept aimed at expanding the benefits of continuous internet connectivity. IoT can be utilized for monitoring the intensity of light, temperature, and air humidity in the surroundings to determine suitable locations for the placement of solar panels. Solar panels are made of semiconductor materials capable of converting solar energy into electricity. The primary issue with using solar panels is that the power output they produce depends on the intensity of light captured by the solar panel. Additionally, the temperature and air humidity around the solar panel also influence its performance. The objective of this research is to create a system for measuring the intensity of sunlight, humidity, and temperature for the placement of IoT-based solar panels using LDR and DHT 11 sensors. The development of this system involves the use of the Prototyping Method. The device's design incorporates the NodeMCU ESP32 microcontroller, and monitoring is conducted through a smartphone using the Blynk application. The LDR and DHT 11 sensors are connected to the NodeMCU ESP32's GPIO as data receivers. A WiFi network is used to transmit intensity of light, temperature, and humidity data from the NodeMCU ESP32 to the smartphone, where it is displayed through the Blynk application. This research is beneficial for identifying the most suitable locations for solar panel placement.Â Keywords : IOT, Solar panel, Monitoring, NodeMCU ESP32, Blynk